Feasibility of Proton Beam Therapy for Infants with Brain Tumours: Experiences from the Prospective KiProReg Registry Study. Issue 7 (July 2021) - Jazmati, D.; Steinmeier, T.; Ahamd Khalil, D.; Frisch, S.; Peters, S.; Schulze Schleithoff, S.; Bäumer, C.; Rutkowski, S.; Frühwald, M.C.; Blase, C.; Tippelt, S.; Timmermann, B.
Abstract: Aims: Proton beam therapy (PBT) has increasingly been applied for the treatment of young children when radiotherapy is needed. The treatment requires intensive multimodality care and is logistically demanding. In this analysis, we evaluated our experiences in treating infants with tumours of the central nervous system with PBT. Materials and methods: Children younger than 2 years of age treated with PBT for central nervous system tumours enrolled in the prospective registry study KiProReg were retrospectively analysed. Information on patient characteristics, treatment, toxicities and outcome were evaluated. Adverse events were classified according to the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE V4.0) before, during and after PBT. Results: Between September 2013 and June 2018, 51 infants were eligible. The median age was 19 months (range 11–23 months) at the time of PBT. Tumour entities were ependymoma (51.0%), atypical teratoid rhabdoid tumour (39.0%), high-grade glioma (6.0%), pineoblastoma (2.0%) and medulloblastoma (2.0%). The prescribed median total dose was 54.0 Gy (range 45.0–59.4 Gy). Most received local radiotherapy. In four patients, craniospinal irradiation followed by a boost to the local tumour bed was applied. The median follow-up time was 42.0 months (range 7.3–86.2 months). The estimated 3-year local control, progression-free survival and overall survival rates for all patients were 62.7, 47.1 and 76.5%, respectively. During radiotherapy, 24 events of higher-grade (CTCAE ≥ °III) toxicities were reported. Interruption of radiotherapy for more than 2 days was due to infection ( n = 3) or shunt complication ( n = 2). Unexpected hospitalisation during radiotherapy affected 12 patients. Late adverse events attributable to radiotherapy included endocrinopathy (CTCAE °II; 7.8%), new onset of hearing loss (CTCAE °III; 5.8%) and visual impairment (CTCAE °IV; 1.9%). Transient radiation-induced imaging changes occurred in five patients (9.8%). Conclusions: Our study indicates that PBT is feasible for very young children with central nervous system tumours, at least in the short term. However, it requires challenging interdisciplinary medical care and high logistical effort. For evaluation of late effects, longer follow-up and evaluation of neurocognitive outcome are desirable. More data have to be gathered to further define the role of radiotherapy in infants over time. Highlights: Proton Beam Therapy for infants with brain tumors is feasible with acceptable acute and late toxicities. Early oncological control rates are promising. Optimal medical care is challenging, requiring flexible logistics and a high multidisciplinary effort. Concurrent chemotherapy and invasive accesses were found to have a high risk for complications during irradiation.